STRATEGI MENGKREASI SOAL KOGNITIF TINGGI (HOTS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN PAI - Malik Akbar Simanullang; Nur Mawaddah Islamiyah; Armai Arief; Ahmad Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to find the main challenges and solutions in developing HOTS questions to improve student’s critical thinking skills in Islamic Religious Education (PAI) learning. HOTS questions in PAI learning can encourage students to think critically and apply Islamic teachings in real life contexts, and also overcome the limitations of memorization-based learning. The method of library research by collecting data from various scientific journals relevant to the research study. So the results of the study obtained that HOTS questions can make students transform from a memorization system to a critical thinking system and can even reach the stage of creating. However, in its implementation there are also several challenges, both from the competence of educators, time and resources, students’ difficulties in adapting, an assessment system that is less supportive, lack of HOTS question references, and lack of support from schools. So that teaching PAI through HOTS questions is not just an option, but a necessity in order to produce a geberation that thinks critically, creatively, and adheres to religious values.